1998
DOI: 10.1097/00006123-199805000-00066
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the Titration Method of Mild Hypothermia in Severely Head-injured Patients with Intracranial Hypertension

Abstract: The titration method of mild hypothermia to control intracranial hypertension in severely head-injured patients is clinically feasible. However, the method failed to reduce the incidence of infectious and hematological complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…We identified a total of 18 studies involving hypothermia for control of ICP; 13 were randomized clinical trials and 5 were observational studies as shown in tables 1 and 2 respectively [54,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. In all studies, the patient populations were comprised of TBI patients with GCS < 9 and an abnormal CT scan.…”
Section: Therapeutic Hypothermia For Icp Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified a total of 18 studies involving hypothermia for control of ICP; 13 were randomized clinical trials and 5 were observational studies as shown in tables 1 and 2 respectively [54,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. In all studies, the patient populations were comprised of TBI patients with GCS < 9 and an abnormal CT scan.…”
Section: Therapeutic Hypothermia For Icp Controlmentioning
confidence: 99%
“…In patients with ICP higher than 20 mmHg, initial (standard) treatment included appropriate sedatives, narcotics, treatment with neuromuscular blockers (for ICP control and/or shivering) and administration of hyperosmolar therapy. Neurosurgical interventions were undertaken when necessary to evacuate subdural lesions or large intracerebral lesions [58,61,63,64,[66][67][68][69][70][71][72][73][74]. In nine studies, there was no mention of the use barbiturates for ICP control [60,62,64,68,69,[71][72][73][74].…”
Section: Therapeutic Hypothermia For Icp Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimierung der sekundären Hirnschä digung infolge Ödembildung und damit verbundener intrakranieller Druckerhö hung zum Ziel. Seit den 1990erJahren wurden mindestens 13 klinische, meist "SinglecenterStudien" bekannt, die den Einfluss der milden HT bei SHT unter sucht haben [8,9,10,11,12,13,14,15,16,17,18,19,20]. Wenngleich die Einschlusskri terien sowie auch die Hypothermie und Aufwärmzeiten z. T. differierten, konnte in nahezu allen Fällen übereinstimmend eine signifikante Senkung des intrakra niellen Druckes ("intracranial pressure", ICP) beschrieben werden.…”
Section: Schädel-hirn-traumaunclassified
“…In addition, the rapid decrease of ICP-induced by hypothermia [18], [20], [21], [23] and [24] suggests that the reduction of cerebral blood flow (CBF) and volume may account to a large part for the effect of hypothermia on ICP. The reduction of ICP has, in turn, beneficial effects on the preservation of brain tissue perfusion and blood-brain barrier integrity.…”
Section: Introductionmentioning
confidence: 99%